Inflammatory features of nasal mucosa in smokers with and without COPD. Issue 4 (26th March 2004) - Vachier, I; Vignola, A M; Chiappara, G; Bruno, A; Meziane, H; Godard, P; Bousquet, J; Chanez, P
Abstract : Background: To investigate whether nasal and bronchial inflammation coexists in chronic obstructive pulmonary disease (COPD), nasal and bronchial biopsy specimens from seven control subjects, seven smokers without COPD, and 14 smokers with COPD were studied. Methods: Nasal and bronchial biopsy specimens were taken from the same patients during bronchoscopy and squamous cell metaplasia and the thickness of the epithelium and basement membrane were measured. The numbers of eosinophils (EG2), neutrophils (elastase), macrophages (CD68), and CD8 T lymphocytes (CD8/144B) were assessed by immunohistochemistry. Results: Smokers with and without COPD had squamous metaplasia in the nasal and bronchial epithelium. In all groups the thickness of the nasal epithelium was greater than that of the bronchial epithelium. The thickness of the basement membrane was similar in nasal and bronchial biopsy specimens from smokers with and without COPD, but was greater in the bronchi than in the nasal epithelium of controls. Eosinophil number was higher in the nasal and bronchial mucosa of smokers without COPD than in smokers with COPD or controls. Neutrophil number was higher in the nasal and bronchial mucosa of smokers with COPD than in smokers without COPD or controls. CD8 T lymphocyte numbers were similar in smokers with and without COPD and higher than in controls. There were fewer macrophages in nasal and bronchial biopsy specimens from smokers without COPD than in those with COPD. Conclusion: Nasal and bronchial inflammation coexists in smokers and is characterised by infiltration of CD8 T lymphocytes. In smokers without COPD this feature is associated with an increased number of eosinophils, while in those with COPD it is linked to an increased number of neutrophils in both nasal and bronchial biopsy specimens.